Treatment for metastatic adenocarcinoma of the stomach and gastroesophageal junction: 2020 - Hsu, Andrew (Ann Transl Med, 2020)
Gastric and gastroesophageal junction (GEJ) cancer is one of the most common malignancy worldwide. In unresectable or metastatic disease, the prognosis is poor and is generally less than a year. Standard front-line chemotherapy includes two- or three-drug regimens with the addition of trastuzumab in HER2-positive disease. With an increased understanding of the biology of cancer over the past few decades, targeted therapies have made their way into the treatment paradigm of many cancers. They been examined in the first- and second-line settings in the treatment of gastroesophageal cancer though has yielded few viable treatment options. One success is ramucirumab either as monotherapy or in combination with paclitaxel is the preferred choice in second-line therapy. While immunotherapy has been considered a breakthrough in oncology over the past decade, the response rates in gastric and gastroesophageal cancers have been relatively low compared to other cancers, resulting in its limited approval and mostly reserved for second-line therapy or beyond. In this article, we will review the standard first- and second-line treatment regimens. Furthermore, this article will review the use of targeted therapies and immunotherapy in treatment of gastric and gastroesophageal cancers. Lastly, we will touch upon future treatment strategies that are currently under investigation.